The impact of military: on character formation, ethical education, and the communication of values in late modern pluralistic societies - Pickard, Stephen K.; Welker, Michael; Witte, John (Evangelische Verlagsanstalt, 2022)
Frontmatter -- Cover -- Titel -- Impressum -- Table of Contents -- Acknowledgments -- Preface to the Series -- Introduction -- Part One: Combatants, Ethics, and Society -- The Military Defense System and the Public Soul in Germany: A Protestant Perspective -- Inner Leadership, or The Soldier's Responsibility for Humanity and Peace -- The Complementary Path to Peace: On Peace Ethics in German Protestantism -- Part Two: Virtues: Re-Evaluating the Military Context -- Which Morals Society Should Learn from the Military, and Which Decidedly Not -- The Indispensability of Virtues in the Military: Virtue Ethical Considerations Following the Guiding Concept of the Miles Protector -- Different Missions, Different Virtues? -- From the Playing Field to the Battlefield: Does Sport in the Military Promote the Formation of a Specific Character? -- After Chivalry -- Part Three: Moral Injury and Character -- Moral Injury, Moral Character, and Military Combatants -- In the Shadow of the Operation: Moral and Spiritual Injuries as New Challenges for Pastoral Care in the German Armed Forces -- Communal Responses to the Business of War -- Backmatter -- Contributors -- Weitere Veröffentlichungen.